2016
DOI: 10.1108/ijchm-09-2014-0448
|View full text |Cite
|
Sign up to set email alerts
|

An integrated model of festival revisit intentions

Abstract: Purpose This paper aims to investigate the determinants of current visitors’ festival revisit intentions. The concepts of festival quality and satisfaction were adapted and integrated with the theory of planned behavior (TPB) from social psychology to theorize a model of festival revisit intentions. In addition, given the importance of social characteristics in festival visiting behavior, the relative impacts of three modes of social influences (i.e. subjective norms, group norms and social identity) were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 86 publications
1
34
1
2
Order By: Relevance
“…Other authors consider loyalty in festival tourism as the predisposition of users to repeat certain behaviour [ 15 ], which implies the intention to attend festivals again [ 26 ] and recommend them to others [ 49 ]. Said repetition has been analysed in the tourism field with regards to loyalty regarding specific destinations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other authors consider loyalty in festival tourism as the predisposition of users to repeat certain behaviour [ 15 ], which implies the intention to attend festivals again [ 26 ] and recommend them to others [ 49 ]. Said repetition has been analysed in the tourism field with regards to loyalty regarding specific destinations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As visitors' interest and involvement increased, their perception of value and satisfaction was raised and contributed to their behavioral intention [48]. Choo, Ahn and Petrick also found that tourist satisfaction is one of the most important factors influencing future purchases and intention to revisit [49]. Satisfied customers become loyal, and this means that many of them will repeat visits in the future [50].…”
Section: Mediation Effectsmentioning
confidence: 99%
“…Therefore, the intention to visit again can be interpreted as continuous satisfaction rather than the initiator of the decision-making process. This can be described as a strong likelihood of revisiting tourist attractions, whether or not with a positive attitude towards service providers (Oliver, 1997;Wu et al, 2015;Baker and Crompton, 2000;Bigné et al, 2005;Bintarti and Kurniawan, 2017;Aziz et al, 2012;Choo et al, 2016;Han et al, 2009;Um et al, 2006). In-depth, the intention to revisit tourist destinations is the willingness to visit repeatedly.…”
Section: Revisit Intentionmentioning
confidence: 99%